A microeconometric analysis of the springboard subsidiary: The case of Spanish firms (2015)
This paper provides a microeconometric analysis of the distinctive characteristics of springboard subsidiaries that have a positive impact on the subsidiaries’ performance. Based on panel data estimations for subsidiaries of European multinational companies with a presence in Spain, the authors found that if the subsidiary is located in the springboard country, then the performance improvement (increase in profit margin) of the subsidiary is about 49 percentage points. When the Spanish subsidiary is considered a springboard subsidiary, its performance is 7.7 percentage points higher than the performance of other subsidiaries that are not springboard subsidiaries. If the subsidiary has a technological relationship with another subsidiary, its performance is 6.7 percentage points higher than the performance of other subsidiaries that do not have a technological relationship. Finally, when the firm has low autonomy, the performance of the subsidiary is 6.2 percentage points lower than that of firms that are independent or have a high level of autonomy. © Author(s) 2015.